BURIAL OF CHILDREN IN LOTE B SITE AND ITS SOCIO-POLITICAL SIGNIFICANCE FOR LOWER LURÍN RIVER VALLEY AT THE END OF EARLY INTERMEDIATE PERIOD - Marsteller, Sara (2012)
The present paper seeks to relate current knowledge of Lima funerary practices with hypotheses regarding the nature and moment of the arrival of the Lima culture to the Lurín Valley. Our central goal is to show that, when integrated into a regional and temporal context, the study of mortuary practices can help to clarify further the socio-political situation on the central coast of Peru between the end of the Early Intermediate Period and the start of the Middle Horizon. We present a contextualized analysis of burials recovered during the 2009 season at the site of Lote B in the Lurín Valley.